Method for preparing silicon nitride ceramic through emulsion system water-based tape casting

Through the water-based casting molding method of the emulsion system, combined with the use of tetramethylammonium hydroxide and the emulsion system, the problem of insufficient viscosity and solid content of the silicon nitride water-based casting slurry is solved, the casting effect and sintering deformation of the silicon nitride ceramic are improved, and the preparation of high density and low shrinkage is achieved.

CN119874382APending Publication Date: 2025-04-25SINOSTEEL LUOYANG INSTITUTE OF REFRACTORIES RESEARCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510000785.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing silicon nitride water-based casting slurry has insufficient viscosity and solid content, resulting in poor casting effect, and there is a problem of large deformation of the silicon nitride ceramics during sintering.

Method used

The emulsion system water-based casting method is adopted, by mixing silicon nitride powder, sintering aid, dispersant and deionized water on a ball mill, adding tetramethylammonium hydroxide as a dispersant and emulsion system as a binder, a slurry with high solids content and good fluidity is prepared, and the sintering deformation is improved through the process of stacking and pressing the blank.

Benefits of technology

The preparation of slurry with high solid content and low viscosity is achieved, and the casting effect and sintering deformation of silicon nitride ceramics are improved. The resulting ceramic has high relative density and low shrinkage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for preparing flaky silicon nitride ceramic through emulsion system water-based tape casting. The emulsion is adopted as a silicon nitride slurry binder and is matched with other binders for tape casting, the system can effectively improve the solid phase content of the slurry, the flowability of the slurry is not reduced, and therefore shrinkage and deformation in the drying and sintering process are reduced. And in the subsequent laminating process, an adhesive does not need to be additionally added, and the layers can be well combined. After tape casting, cutting and overlying are carried out, the prepared silicon nitride green body sheet is high in density and free and controllable in thickness, the silicon nitride green body sheet is buried into silicon nitride powder to be sintered at the normal pressure of 1650 DEG C in the nitrogen atmosphere, and the density of the obtained silicon nitride ceramic sheet can reach 98% or above of the theoretical density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing silicon nitride ceramics by water-based tape-casting molding of an emulsion system, belonging to the technical field of structural ceramic production technology. Background Art

[0002] Silicon nitride (Si3N4) ceramics are ceramic materials with excellent performance, featuring outstanding mechanical properties, thermal conductivity and wave transmission properties. They can simultaneously meet the requirements of various working environments for material structure and function, and have strong competitiveness and great market prospects. Due to their small thickness, sheet ceramics can not only meet the requirements of product integration and volume reduction, but also have the advantages of heat dissipation and wave transmission properties. They have been widely used in substrate materials, multilayer ceramic components, multilayer ceramic capacitors, solid oxide fuel cells, functionally gradient ceramics, textured ceramics and other fields.

[0003] Among the preparation methods of silicon nitride ceramics, the tape casting process is widely used due to its simple equipment and low cost. According to the different solvents selected for the slurry, tape casting can be divided into organic tape casting system and water machine tape casting system. Most organic solvents are toxic and volatile, harmful to the human body, easy to cause environmental pollution, and have safety issues such as flammability, which limits its promotion and application. The water-based tape casting system has poor powder dispersion effect, high viscosity of water-based slurry, and low solid content. The existing silicon nitride water-based tape casting slurry mostly uses polyacrylic acid as a dispersant and polyvinyl alcohol as a binder. The viscosity and solid content of the slurry prepared by it still need to be improved. At the same time, sheet ceramics also have the problems of sintering shrinkage and large deformation. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing silicon nitride ceramics by water-based tape casting in an emulsion system, so that a slurry with high solid content and good fluidity can be obtained, a good tape casting effect can be achieved, and the problem of large sintering deformation of silicon nitride ceramics can be improved.

[0005] The present invention adopts the following technical solutions to achieve the above-mentioned purpose: A method for preparing flaky silicon nitride ceramics by water-based tape casting in an emulsion system comprises the following steps: (1) Preparation of slurry: Silicon nitride powder, sintering aid, dispersant and deionized water are ball-milled and mixed in a planetary ball mill to obtain a preliminary slurry; the ball milling speed is 150-200 r / min, and the ball milling time is 2-6 hours; a binder and a plasticizer are added to the preliminary slurry and stirred and mixed evenly, and a silicon nitride tape casting slurry is obtained after vacuum degassing; the dispersant is tetramethylammonium hydroxide; the binder adopts an emulsion system; (2) Slurry tape casting: Pour the silicon nitride casting slurry into the hopper of the casting machine, spread the slurry on the PET oil film of the carrier after passing through a scraper, set the scraper height to 0.3-1.0 mm, and the casting speed to 0.1-0.6 m / min. Dry the wet tape obtained after casting under the action of a heating plate and a fan, peel off the obtained casting dry tape from the PET oil film, and cut it to obtain a single-layer silicon nitride casting blank; (3) Stacking and pressing of blanks: The cut single-layer silicon nitride casting blanks are stacked in sequence and placed in a mold, and are pressed under a pressure of 30 MPa to 80 MPa for 1 to 2 minutes to obtain a multi-layer silicon nitride casting blank of a certain thickness; (4) Debinding and sintering: The flaky silicon nitride ceramic green body is heated from room temperature to 200-250°C at a heating rate of 0.3-3°C / min in an air atmosphere, and kept warm for 1-3 hours, and then heated from 200-250°C to 600-650°C at a heating rate of 0.3-3°C / min, and kept warm for 1-3 hours, and the binder is debonded under natural cooling; The debinding flaky silicon nitride ceramic blank is placed in a graphite crucible, buried with silicon nitride powder, and sintered at normal pressure in a nitrogen atmosphere. The temperature is increased from room temperature to 1650-1700°C at a heating rate of 2-10°C / min, kept for 2h-6h, and then cooled to 1400-1300°C at a cooling rate of 2-10°C / min. Finally, the sintering is completed under natural cooling to obtain flaky silicon nitride ceramics.

[0006] The particle size of the silicon nitride powder in step 1 is 0.5 μm to 2 μm.

[0007] The sintering aid described in step 1 is a mixture of lithium aluminate powder and yttrium oxide powder, and the mass ratio of lithium aluminate powder to yttrium oxide powder in the sintering aid powder is 2:1.

[0008] In step 1, the mass ratio of silicon nitride powder to dispersant is 100:0.4-0.8; the mass ratio of silicon nitride powder to deionized water is 100:30-50; and the mass ratio of silicon nitride powder to sintering aid powder is 100:12.

[0009] In step 1, the mass ratio of silicon nitride powder to binder is 100:10-20, and the binder is selected from at least one of polymethyl methacrylate emulsion, styrene acrylic emulsion, and ethylene propylene emulsion; the mass ratio of silicon nitride powder to plasticizer is 100:3-6, and the plasticizer is selected from at least one of glycerol and polyethylene glycol.

[0010] The present invention proposes a method for preparing silicon nitride ceramics by water-based tape casting of an emulsion system, wherein tetramethylammonium hydroxide is selected as a dispersant, which can not only significantly improve the electrostatic repulsion between silicon nitride powder particles, thereby facilitating the preparation of a slurry with low viscosity and high solid content, but also provide an alkaline environment for the slurry, thereby slowing down the hydrolysis of silicon nitride powder in water; the present invention selects an emulsion system as a binder, and the addition of the binder will not reduce the fluidity of the slurry, thereby facilitating the preparation of a slurry with low viscosity and high solid content, and reducing shrinkage and deformation during drying and sintering. In addition, no additional binder needs to be added during the subsequent lamination process, and the layers can be well combined; the present invention stacks the cut single-layer silicon nitride tape casting blanks in sequence and puts them into a mold, and obtains a multi-layer silicon nitride blank under pressure, the thickness of which is freely controllable, and the density of the blank is high, which can reach more than 98% of the theoretical density after sintering at normal pressure. DETAILED DESCRIPTION

[0011] For a better understanding of the present invention, the present invention is further described below with reference to examples. However, the protection scope of the present invention is not limited to the description scope of the embodiments. Embodiment 1:

[0012] This example was prepared according to the following steps: 1. Preparation of slurry: 128g of silicon nitride powder, 12g of sintering aid, 0.762g of dispersant and 50g of deionized water were ball-milled on a planetary ball mill at a ball-milling speed of 200r / min for 2h to obtain a preliminary slurry with a volume solid content of 45%; styrene-acrylic emulsion and plasticizer polyethylene glycol were added to the preliminary slurry and stirred to mix evenly, and after vacuum degassing for 15min, a silicon nitride tape casting slurry was obtained; The particle size of the silicon nitride powder is 1.0 μm; the sintering aid powder is a mixture of lithium aluminate powder and yttrium oxide powder, and the mass ratio of lithium aluminate powder to yttrium oxide powder in the sintering aid powder is 2:1; The mass ratio of silicon nitride powder to binder is 100:15; the mass ratio of silicon nitride powder to plasticizer is 100:5; 2. Slurry tape casting: The slurry was poured into the hopper of the tape casting machine. After passing through a scraper, the slurry was spread on the PET oil film of the carrier tape. The scraper height was set to 0.3 mm, and the casting speed was 0.2 m / min. The wet tape obtained after casting was dried under the action of a heating plate and a fan. The obtained cast dry tape was peeled off from the PET oil film and cut to obtain a single-layer silicon nitride casting blank with a thickness of 0.17 mm. 3. Stacking and pressing blanks: The cut single-layer silicon nitride tape-cast blanks were stacked in sequence and placed in a mold, a total of 5 layers, and laminated under a pressure of 50 MPa for 1 minute to obtain a silicon nitride tape-cast blank with a thickness of 0.8 mm; 4. Debinding and sintering: The silicon nitride ceramic blank was heated from room temperature to 200°C at a heating rate of 1°C / min in an air atmosphere, and kept at that temperature for 1 hour, and then heated to 600°C at a heating rate of 0.5°C / min, and kept at that temperature for 2 hours, and then cooled naturally to complete the debinding; The debinding flaky silicon nitride ceramic blank was placed in a graphite crucible, buried with silicon nitride powder, and sintered at normal pressure in a nitrogen atmosphere. The temperature was increased from room temperature to 1650°C at a heating rate of 5°C / min, kept for 4 hours, and then decreased to 1400°C at a cooling rate of 3°C / min. Finally, the sintering was completed under natural cooling. The shrinkage rate of the obtained flaky silicon nitride ceramic was 18% and the relative density was 97%. Embodiment 2:

[0013] This example was prepared according to the following steps: 1. Preparation of slurry: 128g of silicon nitride powder, 12g of sintering aid, 0.762g of dispersant and 50g of deionized water were ball-milled on a planetary ball mill at a ball-milling speed of 200r / min for 2h to obtain a preliminary slurry with a volume solid content of 45%; polymethyl methacrylate emulsion and plasticizer glycerol were added to the preliminary slurry and stirred to mix evenly, and after vacuum degassing for 15min, a silicon nitride tape casting slurry was obtained; The particle size of the silicon nitride powder is 1.0 μm; the sintering aid powder is a mixture of lithium aluminate powder and yttrium oxide powder, and the mass ratio of lithium aluminate powder to yttrium oxide powder in the sintering aid powder is 2:1; The mass ratio of silicon nitride powder to binder is 100:15; the mass ratio of silicon nitride powder to plasticizer is 100:3; 2. Slurry tape casting: The slurry was poured into the hopper of the tape casting machine. After passing through a scraper, the slurry was spread on the PET oil film of the carrier tape. The scraper height was set to 0.3 mm, and the casting speed was 0.1 m / min. The wet tape obtained after casting was dried under the action of a heating plate and a fan. The obtained cast dry tape was peeled off from the PET oil film and cut to obtain a single-layer silicon nitride casting blank with a thickness of 0.17 mm. 3. Stacking and pressing blanks: The cut single-layer silicon nitride tape-cast blanks were stacked in sequence and placed in a mold, with a total of 15 layers, and laminated under a pressure of 60 MPa for 1.5 minutes to obtain a silicon nitride tape-cast blank with a thickness of 2.2 mm; 4. Debinding and sintering: The silicon nitride ceramic blank was heated from room temperature to 200°C at a heating rate of 0.5°C / min in an air atmosphere, and kept at that temperature for 2 hours, and then heated to 650°C at a heating rate of 0.5°C / min, and kept at that temperature for 3 hours, and then cooled naturally to complete the debinding; The debinding flaky silicon nitride ceramic blank was placed in a graphite crucible, buried with silicon nitride powder, and sintered at normal pressure in a nitrogen atmosphere. The temperature was increased from room temperature to 1680°C at a heating rate of 3°C / min, kept for 4 hours, and then decreased to 1300°C at a cooling rate of 3°C / min. Finally, the sintering was completed under natural cooling. The shrinkage rate of the obtained flaky silicon nitride ceramic was 17% and the relative density was 95%. Embodiment 3:

[0014] This example was prepared according to the following steps: 1. Preparation of slurry: 128g of silicon nitride powder, 12g of sintering aid, 0.762g of dispersant and 50g of deionized water were ball-milled on a planetary ball mill at a ball-milling speed of 200r / min for 2h to obtain a preliminary slurry with a volume solid content of 45%; polymethyl methacrylate emulsion and plasticizer glycerol were added to the preliminary slurry and stirred to mix evenly, and after vacuum degassing for 15min, a silicon nitride tape casting slurry was obtained; The particle size of the silicon nitride powder is 1.0 μm; the sintering aid powder is a mixture of lithium aluminate powder and yttrium oxide powder, and the mass ratio of lithium aluminate powder to yttrium oxide powder in the sintering aid powder is 2:1; The mass ratio of silicon nitride powder to binder is 100:15; the mass ratio of silicon nitride powder to plasticizer is 100:3; 2. Slurry tape casting: The slurry was poured into the hopper of the tape casting machine. After passing through a scraper, the slurry was spread on the PET oil film of the carrier tape. The scraper height was set to 0.5 mm, and the casting speed was 0.2 m / min. The wet tape obtained after casting was dried under the action of a heating plate and a fan. The obtained cast dry tape was peeled off from the PET oil film and cut to obtain a single-layer silicon nitride casting blank with a thickness of 0.26 mm. 3. Stacking and pressing blanks: The cut single-layer silicon nitride tape-cast blanks were stacked in sequence and placed in a mold, a total of 5 layers, and laminated under a pressure of 50 MPa for 1 minute to obtain a silicon nitride tape-cast blank with a thickness of 1.2 mm; 4. Debinding and sintering: The silicon nitride ceramic blank was heated from room temperature to 200°C at a heating rate of 0.8°C / min in an air atmosphere, and kept at that temperature for 2 hours. The temperature was then raised to 650°C at a heating rate of 0.8°C / min, and kept at that temperature for 2 hours. The temperature was then naturally cooled to complete the debinding. The debinding flaky silicon nitride ceramic blank was placed in a graphite crucible, buried with silicon nitride powder, and sintered at normal pressure in a nitrogen atmosphere. The temperature was increased from room temperature to 1650°C at a heating rate of 2°C / min, kept for 4 hours, and then decreased to 1300°C at a cooling rate of 3°C / min. Finally, the sintering was completed under natural cooling. The shrinkage rate of the obtained flaky silicon nitride ceramic was 15% and the relative density was 93%.

[0015] The temperature was raised from room temperature to 1650-1700°C at a heating rate of 2°C / min-10°C / min, and kept for 2h-6h. The temperature was then lowered from 1650-1700°C to 1400-1300°C at a cooling rate of 2°C / min-10°C / min. Finally, the sintering was completed under natural cooling, and the shrinkage rate of the obtained silicon nitride sheet ceramics was 15% and the relative density was 93%.

Claims

1. A method for preparing sheet-like silicon nitride ceramics by water-based tape casting in an emulsion system, characterized in that: The following steps are involved: (1) Preparation of slurry: Silicon nitride powder, sintering aid, dispersant and deionized water are ball-milled and mixed in a planetary ball mill to obtain a preliminary slurry; the ball milling speed is 150-200 r / min, and the ball milling time is 2-6 hours; a binder and a plasticizer are added to the preliminary slurry and stirred and mixed evenly, and a silicon nitride tape casting slurry is obtained after vacuum degassing; the dispersant is tetramethylammonium hydroxide; the binder adopts an emulsion system; (2) Slurry tape casting: Pour the silicon nitride casting slurry into the hopper of the casting machine, spread the slurry on the PET oil film of the carrier after passing through a scraper, set the scraper height to 0.3-1.0 mm, and the casting speed to 0.1-0.6 m / min. Dry the wet tape obtained after casting under the action of a heating plate and a fan, peel off the obtained casting dry tape from the PET oil film, and cut it to obtain a single-layer silicon nitride casting blank; (3) Stacking and pressing of blanks: The cut single-layer silicon nitride casting blanks are stacked in sequence and placed in a mold, and are pressed under a pressure of 30 MPa to 80 MPa for 1 to 2 minutes to obtain a multi-layer silicon nitride casting blank of a certain thickness; (4) Debinding and sintering: The flaky silicon nitride ceramic green body is heated from room temperature to 200-250°C at a heating rate of 0.3-3°C / min in an air atmosphere, and kept warm for 1-3 hours, and then heated from 200-250°C to 600-650°C at a heating rate of 0.3-3°C / min, and kept warm for 1-3 hours, and the binder is debonded under natural cooling; The debinding flaky silicon nitride ceramic blank is placed in a graphite crucible, buried with silicon nitride powder, and sintered at normal pressure in a nitrogen atmosphere. The temperature is increased from room temperature to 1650-1700°C at a heating rate of 2-10°C / min, kept for 2h-6h, and then cooled to 1400-1300°C at a cooling rate of 2-10°C / min. Finally, the sintering is completed under natural cooling to obtain flaky silicon nitride ceramics.

2. The method for preparing a sheet-like silicon nitride ceramic according to claim 1, characterized in that: The particle size of the silicon nitride powder in step 1 is 0.5 μm to 2 μm.

3. The method for preparing a sheet-like silicon nitride ceramic according to claim 1, characterized in that: The sintering aid described in step 1 is a mixture of lithium aluminate powder and yttrium oxide powder, and the mass ratio of lithium aluminate powder to yttrium oxide powder in the sintering aid powder is 2:

1.

4. The method for preparing a sheet-like silicon nitride ceramic according to claim 1, characterized in that: In step 1, the mass ratio of silicon nitride powder to dispersant is 100:0.4-0.8; the mass ratio of silicon nitride powder to deionized water is 100:30-50; and the mass ratio of silicon nitride powder to sintering aid powder is 100:

12.

5. The method for preparing a sheet-like silicon nitride ceramic according to claim 1, characterized in that: In step 1, the mass ratio of silicon nitride powder to binder is 100:10-20, and the binder is selected from at least one of polymethyl methacrylate emulsion, styrene acrylic emulsion, and ethylene propylene emulsion; the mass ratio of silicon nitride powder to plasticizer is 100:3-6, and the plasticizer is selected from at least one of glycerol and polyethylene glycol.